Escherichia coli spp, Staph albus and Klebseilla spp were affected by some Antibiotics for Urinary Tract Infections in Bani Waleed City - Alla Abdulmutalib Mohammed; Abdul Samad; Ola Adrees Omar (Brilliance: Research of Artificial Intelligence, 2022)
In a statistical research of 100 women diagnosed with urinary tract infections (UTIs) at Al Dhahirah Hospital - Ibn Sina Clinic - Aqaba Laboratory for Medical Analysis in the city of Bani Waleed in 2017, Agrahl (Ibrahim, H. K., Mohammed, A. A., & Omar, O. A. (2018).) and (Ibrahim, Hamza Khalifa). (2017). found that the most affected age group is the most common. The illness afflicted (26-30) years by 39 percent, making it the most affected age group when compared to others. The antibiotic (Augmentin) was shown to be the most important and effective antibiotic used in the treatment of urinary tract infection during this time period, accounting for 49 percent of cases, while UTI is more frequent in the winter, with a 59 percent infection rate. The increasing resistance to bacteria of our isolates under investigation might be related to the widespread use of antibiotics at random, allowing for a rise in bacterial resistance to various antibiotics.